2014
DOI: 10.1136/annrheumdis-2014-205212
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis, psoriatic arthritis and risk of gout in US men and women

Abstract: Objective Individuals with psoriasis have been found to have increased blood levels of uric acid. However, there is no prospective data on the association between psoriasis and uric acid levels and subsequent development of gout. In this study, we examined the risk of gout among individuals with psoriasis and psoriatic arthritis (PsA) in two cohorts of men and women, the Health Professionals Follow-up Study (HPFS) (1986-2010) and Nurses' Health Study (NHS) (1998-2010). Methods A total of 27,751 men and 71,05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 48 publications
5
62
1
5
Order By: Relevance
“…Further, recent reports have recognized yet additional comorbidities associated with gout, including obstructive sleep apnea and psoriasis 9,10 . One by-product of the cumulative nature of these gout-comorbidity reports is to prompt consideration of the directionality of the association.…”
mentioning
confidence: 99%
“…Further, recent reports have recognized yet additional comorbidities associated with gout, including obstructive sleep apnea and psoriasis 9,10 . One by-product of the cumulative nature of these gout-comorbidity reports is to prompt consideration of the directionality of the association.…”
mentioning
confidence: 99%
“…There are case reports in the literature describing the simultaneous occurrence of psoriasis and gout [1,[5][6][7]. These reports have revealed that the risk of gout is increased with psoriasis, particularly among patients with PsA [4]. However, there are conflicting reports regarding this finding.…”
Section: Introduction __________________________mentioning
confidence: 73%
“…Several reports have described the association of psoriasis with metabolic derangements such as metabolic syndrome and hyperuricemia [2,3]. Psoriatic arthritis ((PsA) is an inflammatory seronegative arthritis which can occur in up to one-fourth of patients with psoriasis [4]. There are case reports in the literature describing the simultaneous occurrence of psoriasis and gout [1,[5][6][7].…”
Section: Introduction __________________________mentioning
confidence: 99%
“…Алкоголизм, ожирение, курение [7][8][9] повышают риск развития псориаза. Различные по-ражения сердечно-сосудистой, эндокринной систе-мы, заболевания печени и желчевыводящих путей, желудочно-кишечного тракта относятся к числу ча-стых сопутствующих заболеваний [10][11][12][13][14][15][16][17][18][19][20]. При псориазе отмечен повышенный риск возникнове-ния некоторых злокачественных новообразований [21].…”
Section: Discussionunclassified
“…У пациентов с псориазом доказан высокий риск сахарного диабета, подагры, воспалительных забо-леваний желудочно-кишечного тракта и желчевы-водящих путей, болезни Крона [16][17][18][19][20].…”
Section: ключевые слова: псориаз заболеваемость распространенностьunclassified